Pertanggungjawaban Ahli Waris Notaris yang Meninggal Dunia dan Penerima Protokol Notaris di Kabupaten Labuhanbatu: (Studi atas Minuta Akta Notaris yang Hilang) - Marudut Gultom; Hasim Purba; Henry Sinaga (CV Rewang Rencang, 2025)
The case of the loss of minutes of a notary's deed who died in Labuhanbatu Regency has raised serious legal problems related to the accountability and legal protection of the parties. Based on normative legal research with a descriptive analytical approach through literature studies and interviews with three Notaries in Labuhanbatu Regency, it was concluded that the responsibility is divided between the notary's heirs who are obliged to report the loss to the MPD, make a report, and submit the remaining protocol, and the notary receiving the protocol who is fully responsible for storing and managing the protocol based on Article 65 of the UUJN. Legal protection for the parties can be obtained through the creation of a replacement deed (Article 57 of the UUJN), court decisions, compensation claims, and assistance from the MPD in reconstructing the deed while maintaining the rights of the parties to obtain complete information about the handling of the loss case.